PENENTUAN KUALITAS AIR DI PERAIRAN TONGGING KECAMATAN MEREK KABUPATEN KARO PROVINSI SUMATERA UTARA - Syafridahannum Rangkuti; Pindi Patana; Syammaun Usman (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Tongging is one of Lake Toba area which is used as a tourism area, ferry ports and floating net cage aquaculture activities which could effect water quality in Tongging. The research aims to determine the value of the parameter of physic, chemistry, biology and water quality based on the quality standard PP RI No. 82/2001 on water quality management and water pollution control. This research was done in Mei to Juni 2017. The study used purposive random sampling method. Station used consistend of the first station (port), the second station (cages), the third station (control). Value parameter of physics, chemistry and biology, among others temperature 24,6oC–26oC, TDS 135-145 mg/l, brightness 9,3-16,6 m, pH 6,3-7,3, DO 4,76-6,3 mg/l, BOD5 0,46-2,46 mg/l, nitrate 0,5 mg/l, phosphote 0,14-0,33 mg/l, total coliform 1053–3566 MPN/100ml. Water quality based on standard class one and class two is being internely polluter with respective value are -30 and -11, while based on standard class three is not polluted or meet quality standard value.Key Word : Water quality, Storet method, Tongging waters.